Exposure to hydrogen peroxide – under the toxicologist eye - Boreński, Grzegorz; Wójcik, Magdalena; Poleszak, Julita; Szabat, Przemysław; Szabat, Marta; Tchórz, Michał; Szponar, Jarosław (Journal of Education, Health and Sport, 2019)
Introduction: Hydrogen peroxide is well soluble, odourless and colourless liquid with syrup consistency. It has different application depending on concentration. In 3% of concentration is present in almost every home as a disinfectant product, in higher concentration (35%) is used in pharmaceutical, chemical and cosmetic industry. The aim of the study: The purpose of this systemic review was to collect and analyse causes and possibilities of treatment a patient after ingestion a caustic substance.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar database was carried out using the following keywords: hydrogen peroxide, exposure, toxicology.Description of the state of knowledge: Exposure for hydrogen peroxide is not very common and most of the times is unintentional, except suicide attempts. Because it is a caustic substance and the main route of exposure is ingestion, most of symptoms are due to damage of gastrointestinal tract. However, the consequences of exposure range from short-time illness to brain damage or even death.Summary: Patient after exposure to >30% hydrogen peroxide should receive a complex treatment. Physicians need to be alert to the symptoms of not only gastrointestinal tract but also CNS. The patient may require specialized care by many specialists.